Accelerating food production in Sub-Saharan Africa - Mellor, John W.; Delgado, Christopher L.; Blackie, Malcom J. (International Food Policy Research Institute, 1987)
The final papers-the chapters herein-provide a wide-ranging, up-todate, and varied approach to key issues, which reflect the diverse physical, cultural, economic, and political environment of Africa. Recognition of this diversity is essential to grasping the magnitude of the problem of accelerating food production in Africa and to setting the essential priorities. In Africa, differences in perception as to developmental needs and the initial conditions necessary for development are greater than elsewhere because of the wide gaps in knowledge that characterize the region. Many of these differences are reflected in the chapters in this book. Food policy is, of course, the product of political processes. And the environments of these political actors are subtly reflected in their points of view. We have attempted to catch these nuances in this volume.